A misticall deuise of the spirituall and godly loue betwene Christ the spouse, and the church or congregation Firste made by the wise Prince Salomon, and now newly set forth in verse by Iud Smith. Wherunto is annexed certeine other briefe stories. And also a treatise of prodigalitie, most fit and necessarie to be read [and] marked of all estates. 1575 - Smith, Jude; Wharton, John schoolmaster; Carr, John citezein of London (Imprinted at London By Henry Kirckham, and are to be solde at his shoppe, at the little northe doore of Paules, at the signe of the black Boie, 1575)
eebo-0018
In two parts; part 2 is a reissue of STC 4685: Carr, John. The ruinous fal of prodigalitie; it retains that title page
Signatures: A-B C³+
Reproduction of the original in the British Library
Dedication signed: John Wharton
STC (2nd ed.), 22805
Copy catalogued lacks part 2
Keywords: Christian Life -- Early works to 1800